The Youth Patient and Public Involvement Café-A youth‐led model for meaningful involvement with children and young people - Abigail Thomson; Edward Peasgood; Sam Robertson (Wiley, 2022)
Abstract Introduction There are few meaningful frameworks or toolkits that exist for involvement with young people. Coproduction is a more recent patient and public involvement (PPI) approach that emphasizes the importance of power‐sharing, to set young people as equal partners in the research process. This paper explores the successes and challenges encountered by one coproduced PPI space for young people. Methods This paper is written by a team of young people who developed and worked on the Youth PPI Café over a period of 18 months. It explores how we developed a youth‐led space for involvement in research. The authors have reflected on their experiences, providing examples of how youth PPI and coproduction were delivered in the NHS, in practice. Results By working 'with' young people, rather than 'for' them, we offer insights into the successes and challenges of an entirely youth‐led involvement space. Despite being effective in shaping mental health research for children and young people, we faced challenges with tokenism, resourcing and diversity and inclusion. Conclusions Involving youth meaningfully in research has the potential to inform studies at a macro‐ and microlevel, enabling positive change within research and within the systems that support young people. Patient or Public Contribution Young people aged 16-24 years with lived experience were included at every stage of this project, from formulation to the delivery and development of the group, to the preparation of this manuscript and its dissemination. Sussex Partnership NHS Foundation Trust's charity 'Heads On' provided funding for this study.